High pressure trace element partitioning between clinopyroxene and alkali basaltic melts. (15th July 2021) - Bonechi, Barbara; Perinelli, Cristina; Gaeta, Mario; Fabbrizio, Alessandro; Petrelli, Maurizio; Strnad, Ladislav
Highlights: Trace elements partition coefficients ( D ) between clinopyroxene and primitive K-basalts. Influence of temperature, chemical composition and growth rate on D. Less efficient rejection of incompatible elements during rapid crystal growth. Apparent increase in D REE values with time imputable to melt polymerization. Deep differentiation of Campi Flegrei Volcanic District parental magmas linked to fractionation of 20–30% of a clinopyroxenitic mineral assemblage. Abstract: We present new experimental data on major and trace element partition coefficients ( D ) between clinopyroxene and a K-basaltic melt from Procida Island (Campi Flegrei Volcanic District, south Italy). Time-series experiments were conducted at 0.8 GPa and 1080–1250 °C aiming to investigate the role of the crystallization kinetics on trace elements partitioning behaviour at a pressure relevant for deep magmatic reservoirs. Results indicate that large ion lithophile elements (LILE) are incompatible (e.g., D Sr  ≤ 0.15), light rare elements (LREE; e.g., D La  ≤ 0.20) are always more incompatible than heavy rare elements (HREE), which in some cases result to be compatible with clinopyroxene (e.g., D Dy  = 1.40); high field strength elements (HFSE) are generally incompatible ( D HFSE  ≤ 0.8), while transition elements (TE) range from slightly incompatible (e.g., D V  = 0.6) to highly compatible (e.g., D Cr  = 63). The calculated D values for LILEs, REEs, HFSEs, and TEs tend to decrease with the increase of temperature and to increase with increasing tetrahedrally-coordinated aluminium content, in agreement with the previous studies. Moreover, we observed the influence of the growth rate on the partition coefficients, with the highest D REE values calculated in the runs with the highest growth rate (~10 −7 cm s −1 ), due to the less efficient rejection of incompatible elements during rapid crystal growth, that in this study is not linked to disequilibrium conditions, but to the presence of pre-existing nuclei. Additionally, the apparent increase in D REE values with time observed in some runs is not referable to a change in time but rather to the different degrees of polymerization, expressed as the ratios NBO/T of these melts, strictly related to a loss of Fe occurred during the experiments, and thus to a different melt viscosity. Finally, the application of the experimental clinopyroxene-melt partition coefficients highlights that the deepest step of the magmatic differentiation in the Campi Flegrei Volcanic District is represented by the fractionation of about 20–30% of a clinopyroxenitic mineral assemblage from a basaltic parental magma.